2023
DOI: 10.1007/s44196-023-00189-7
|View full text |Cite
|
Sign up to set email alerts
|

Design of Customized Garments Towards Sustainable Fashion Using 3D Digital Simulation and Machine Learning-Supported Human–Product Interactions

Abstract: This paper put forward a new interactive design approach for customized garments towards sustainable fashion using machine learning techniques, including radial basis function artificial neural network (RBF ANN), genetic algorithms (GA), probabilistic neural network (PNN), and support vector regression (SVR). First, RBF ANNs were employed to estimate the detailed human body dimensions to fulfill consumers’ ergonomics requirements. Next, the GA-based models were developed to generate the formalized design solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 51 publications
0
1
0
1
Order By: Relevance
“…The study found that this approach leverages hybrid feature selection and the Bayesian search to enhance the performance of random forest (RF) and XGBoost 0.72, particularly in filling in missing data, where RF outperforms XGBoost. Wang et al [17] introduced an approach that utilizes multiple machine learning frameworks, including RBF-NN, GA, PNN (probabilistic neural network), and SVR, for interactive personalized clothing design. This method enhanced the capability of personalized clothing design by estimating body dimensions, generating customized design solutions, quantifying consumer preferences, predicting clothing fit, and self-adjusting design parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The study found that this approach leverages hybrid feature selection and the Bayesian search to enhance the performance of random forest (RF) and XGBoost 0.72, particularly in filling in missing data, where RF outperforms XGBoost. Wang et al [17] introduced an approach that utilizes multiple machine learning frameworks, including RBF-NN, GA, PNN (probabilistic neural network), and SVR, for interactive personalized clothing design. This method enhanced the capability of personalized clothing design by estimating body dimensions, generating customized design solutions, quantifying consumer preferences, predicting clothing fit, and self-adjusting design parameters.…”
Section: Introductionmentioning
confidence: 99%
“…В світі починають використовуватися нові інтерактивні підходи до дизайну одягу на замовлення з використанням методів машинного навчання і штучного інтелекту [9]. В статті [10] описані можливості віртуальної реальності і штучного інтелекту, але відзначено, що творці моди не завжди володіють технічними та виробничими навичками або знаннями для їх ефективного використання.…”
unclassified